Comparison of Morula and Blastula Embryo Vitrification by Using Cryoprotectant Ethylene Glycol, Propanediol, DMSO and Insulin Transferrin Selenium - Widjiati, Widjiati; Luqman, Epy Muhammad; Sumarsono, Portia (KnE Life Sciences, 2017)
Vitrification is freezing method with low temperature (-196ºC) using high concentrations of cryoprotectants with a view to preventing the formation of ice crystals that can damage cells and decrease the viability of the embryo blastomeres. Embryos post warming which has low viability when transferred to a recipient will decrease the pregnancy rate. Intracellular cryoprotectants used in vitrification is ethylene glycol, propanediol, or DMSO. The third type of cryoprotectants has different capacities to protect the morula and blastocyst stage embryos. This study aims to decide the exact type of cryoprotectants in protecting the morula and blastocyst stage embryos when vitrification process. Research methods were divided into three groups of cryoprotectants that group treatment 1 (P1): Ethylene Glycol 30% + Sucrose 1 M + Insulin Transferrin Selenium 15 mL, group treatment 2 (P2): Propanediol 30% + Sucrose 1 M + Insulin Transferrin Selenium 15 mL, treatment Group 3 (P3): DMSO 30% + Sucrose 1 M + Insulin Transferrin Selenium 15 mL. The data obtained were analyzed by one-way ANOVA. Results of research that use Propanediol at the morula stage embryo vitrification is not significantly different from the Ethylene glycol but significantly different from DMSO. Then use Ethylene Glycol at the blastocyst stage embryo vitrification significantly different with Propanediol and DMSO and DMSO Propanediol but usage is no different. The conclusion of this study is Propanediol used as cryoprotectants in the vitrification process morula stage embryos, while ethylene glycol used as cryoprotectants the blastocyst stage embryo vitrification process. Keywords: vitrification; ethylene glycol; propanediol; DMSO; morula; blastocyst